Fertility Status of Married Women and Its Determinants in Ethiopia - Muluneh, Essey Kebede; Zewotir, Temesgen; Yayeh, Tilaye Matebe (Journal of Economics and Behavioral Studies, 2016)
This study investigates determinant factors of fertility among married women in Ethiopia, the second most populous country in Africa with rapid population growth. The data used for the analysis was obtained from the 2014 Ethiopia Mini Demographic and Health Survey which was carried out by the Central Statistical Agency. A generalized linear model (GLM) analysis was carried out to investigate the effect of socioeconomic and demographic factors on the number of children ever born by a married woman of age 15-49 years. High fertility was independently associated with residing in urban areas, increased household economic status, younger age at first birth and not using contraceptives. Current age and media exposure, household head gender and media exposure, household head gender and regional state, mother’s education and, regional state and media exposure and regional state were found to jointly affect fertility level.